Cracking the nonverbal code: analysing cultural artefacts of the BaTonga in Zimbabwe - Saidi, Umali (Midlands State University, 2017)
This thesis cracks open three BaTonga artefacts, the ncelwa (smoking pipe), buntibe (orchestral drum) and Nyaminyami Walking Stick (wooden sculpture) as the key nonverbal visual codes in the visual cultural communication of BaTonga in Zimbabwe. Using artefactual ethnisemiotics, the study shows how visual cultural communication is played out and is used by the BaTonga in negotiating for socio-cultural space in Zimbabwe. BaTonga historical experiences show characterisation of displacement and a continued struggle to uphold their identity and culture. Their experiences along the Zambezi valley as well as redefinition of their livelihoods in the new arid terrain far removed from the Zambezi, given the construction of the Kariba hydroelectric power project, has for long contributed among other forces to their marginalisation. To assert their visibility, the BaTonga have subtlety used various visual means to negotiate for space in the country. This thesis, thus, critiques three BaTonga cultural artefacts showing how significant they are in the communicative cultural life of the BaTonga in Zimbabwe. In making this analysis and exploration, the study makes a reflection of how BaTonga represent themselves visually in their culture and even outside their own cultural boundaries. To critique the Tongan cultural communication is also a process of generating an understanding of how the BaTonga project their identity and de-marginalisation. Cultural survival of these people, against other ethnic groups in Zimbabwe is crucial for them and for Zimbabwe in that, as the study demonstrates, the barometer of population which has also been used to justify continued dominance of the BaTonga by the Shona or Ndebele in the country is but null and void. The study advances artefactual ethnisemiotics as an alternative approach to artefacts and visual communication; areas which have also received little attention in the country and even in the region. Through artefactual ethnisemiotics, the study shows that everyday objects are important visual ethnisemiotic pieces that embody a great deal of meanings from which construction of cultural messages are made possible by users. Focus on everyday objects in use brings in new approaches to the study of visual cultural communication, heritage and broadly cultural studies in that, before archaeologists or anthropologists can wait to dig the pieces and characterise them as ossified pieces of history, artefactual ethnisemiotics allows resuscitation, appreciation as well as documentation of a living culture performed in visual communicative ways.